B-cell malignancies treated with targeted drugs and SARS-CoV-2 infection: A European Hematology Association Survey (EPICOVIDEHA) - Infante, Maria Stefania; Salmanton-García, Jon; Fernández-Cruz, Ana; Marchesi, Francesco; Jaksic, Ozren; Weinbergerová, Barbora; Besson, Caroline; Duarte, Rafael F; Itri, Federico; Valković, Toni; Szotkovski, Tomáš; Busca, Alessandro; et al. (Frontiers Media SA, 2022)
Patients with lymphoproliferative diseases (LPD) are vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Here, we describe and analyze the outcome of 366 adult patients with chronic lymphocytic leukemia (CLL) or non-Hodgkin Lymphoma (NHL) treated with targeted drugs and laboratory-confirmed COVID-19 diagnosed between February 2020 and January 2022. Median follow-up was 70.5 days (IQR 0-609). Most used targeted drugs were Bruton-kinase inhibitors (BKIs) (N= 201, 55%), anti-CD20 other than rituximab (N=61, 16%), BCL2 inhibitors (N=33, 9%) and lenalidomide (N=28, 8%).Only 16.2% of the patients were vaccinated with 2 or more doses of vaccine at the onset of COVID-19. Mortality was 24% (89/366) on day 30 and 36%(134/366) on the last day of follow-up. Age >75 years (p<0.001, HR 1.036), active malignancy (p<0.001, HR 2.215), severe COVID-19 (p=0.017, HR 2.270) and admission to ICU (p<0.001, HR 5.751) were risk factors for mortality at last day of follow up. There was no difference in OS rates in NHL vs CLL patients (p=0.306), nor in patients treated with or without BKIs (p=0.151). Mortality in ICU was 66% (CLL 61%, NHL 76%). Overall mortality rate decreased according to vaccination status, being 39% in unvaccinated patients, 32% and 26% in those having received one or two doses, respectively, and 20% in patients with a booster dose (p=0.245). Overall mortality rate dropped from 41% during the first semester of 2020 to 25% at the last semester of 2021. These results show increased severity and mortality from COVID-19 in LPDs patients treated with targeted drugs.